Penguatan Kapasitas Masyarakat dalam Mewujudkan Ketahanan Pangan di Gampong Purwosari Kabupaten Nagan Raya - Mardaleta Mardaleta; Munandar Munandar; Dewi Fithria; Maiza Duana; Yovhandra Ockta; Tya Ulfa; Ranita Suri Dewi; Salma Alfina Putri Nada; Kamalia Ulfa; Tsamarah Nur Rahmah; Wanda Ramadhana (Universitas Teuku Umar, 2026)
Food security issues in marginal villages such as Purwosari Village, Nagan Raya Regency, require a collaborative and sustainable multi-stakeholder approach. This village has the potential for local food sources such as tempeh, water spinach, spinach, and mustard greens, but faces challenges such as marginal land conditions, limited access to capital, and low utilization of promotional technology. The community service activity carried out by ORMAWA HIMAKESMAS of Teuku Umar University (UTU) aims to strengthen food security through participatory, educational, and innovative approaches. The program involved academics, village government, financial institutions (Bank Mustaqim), and the UTU Business Incubator through socialization, training, and interactive discussions. The materials delivered included balanced nutrition based on local food, Islamic financing using the musyarakah scheme, product promotion techniques through creative videos, and integrated village development planning. The results showed an increase in community knowledge regarding the utilization of local food and access to capital, as well as the establishment of a partnership model that can be replicated in other villages. Capacity building and support in terms of policy and infrastructure are key to sustainability. This collaboration between UTU and HIMAKESMAS demonstrates the importance of cross-sector synergy in building food self-sufficient, prosperous, and competitive villages.